2009
DOI: 10.1185/03007990903368310
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and long-term tolerability of sublingual fentanyl orally disintegrating tablet in the treatment of breakthrough cancer pain

Abstract: Sublingual fentanyl ODT was efficacious and well-tolerated for the treatment of BTcP in opioid-tolerant patients with cancer. Sublingual fentanyl ODT provided significant improvements in pain intensity compared to placebo, from 10 min post-administration and throughout the 60-min post-dose assessment period. Sublingual fentanyl ODT was well tolerated over 12 months of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 10 publications
1
91
0
7
Order By: Relevance
“…SDs are dispersions of one or more active pharmaceutical ingredients (API) in an inert carrier or matrix such as biodegradable polymers in solid state, prepared by melting (fusion), solvent, or a melting-solvent method (Chiou, Riegelman, 1971). It has been suggested that orally disintegrating tablets (ODT) have a faster onset of action compared to conventional tablets, and are more appropriate for the treatment of acute pain (Rauck et al, 2009). In addition, ODTs could reduce dysphagia in older patients suffering from arthritis (Shen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…SDs are dispersions of one or more active pharmaceutical ingredients (API) in an inert carrier or matrix such as biodegradable polymers in solid state, prepared by melting (fusion), solvent, or a melting-solvent method (Chiou, Riegelman, 1971). It has been suggested that orally disintegrating tablets (ODT) have a faster onset of action compared to conventional tablets, and are more appropriate for the treatment of acute pain (Rauck et al, 2009). In addition, ODTs could reduce dysphagia in older patients suffering from arthritis (Shen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sublingual fentanyl (SLF) was assessed in cancer patients in a long-term safety phase of 12 months for the management of BTP. Only one patient dropped out for a serious adverse effect considered as possibly related to study medication [42].…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy was based on a general impression regarding the efficacy of INFS with the following scale: 1 (poor), 2 (acceptable), 3 (good), 4 (very good), 5 (excellent). [42]. Quality of sleep was rated with the following scale: 0 (disturbed), 1 (frequent arousals), 2 (good), 3 (very good).…”
Section: Methodsmentioning
confidence: 99%
“…Overall bioavailability is 54%. In a randomized placebo-controlled study of fentanyl sublingual tablets in 131 adult patients with btcp, use of the tablets resulted in significant improvements in pain intensity and relief compared with placebo 66 . In phase iii studies evaluating the long-term effectiveness of transmucosal immediate-release fentanyl, patients reported high levels of satisfaction with the formulation 65,67 .…”
Section: Contemporary Approaches To the Management Of Btcp With Rapidmentioning
confidence: 99%
“…It has a bioavailability of approximately 89% 68 . Its onset of action occurs within approximately 7 minutes, and its duration of analgesic effect is approximately 1 hour 66 . The efficacy of intranasal fentanyl spray 50-200 μg per spray was demonstrated in a phase iii randomized trial that included 120 opioid-tolerant patients with btcp 69 .…”
Section: Contemporary Approaches To the Management Of Btcp With Rapidmentioning
confidence: 99%